Detection of polymorphisms and fecundity determination in Axis axis Erxleben, Rusa timorensis Blainville and Rusa unicolor Kerr raised in Lenggong, Perak, Malaysia - Yahaya, Muhammad Sanusi (2020)
In animal breeding and conservation programmes selection is usually based on fecundity traits. Selection methods such as the traditional marker-assisted selection, which is based on observable phenotypes and genomic selection, which uses genomic features for selection and it can be genome-wide scanning or the candidate gene approach are employed. These candidate genes are polymorphic and their polymorphism is associated with traits of interest. Polymorphisms in form of SNPs and RFLPs have been employed to select animals for breeding and or conservation. This study is therefore, aimed at discovering polymorphisms in the protein-coding region of five fecundity genes: BMP15, FOXL2, GDF9, MHCDQA1 and MTNR1A in Axis axis Erxleben, Rusa timorensis Blainville and Rusa unicolor Kerr reared at PTH Lenggong. This study applied cytogenetic methods to detect morphological and numeric chromosomal aberrations in three breeds of deer comprising 60 individuals. Following the discovery of chromosomal aberrations, DNA was obtained from 45 individuals to amplify the protein coding regions of the fecundity genes, through high fidelity PCR. The genes were confirmed by mapping on metaphase chromosomes through Fluorescent in situ Hybridization (FISH). The PCR products were thereafter sequenced by Sanger’s method. Following sequencing, a combination of Bioinformatic tools were used to detect SNPs and RFLPs in the fecundity genes. The genes were translated into proteins and analyzed for structure and function. Prediction programs and phylogenetic analysis were used to generate wild type proteins, which were used as templates to predict protein structure and the effect of amino acid substitutions on protein function. Fifteen of the 60 animals were found to carry chromosome aberrations. High fidelity PCR produced 225 sequences, which were confirmed by FISH and used in the downstream analysis. A total of 117 SNPs and 13 restriction sites with utility in animal selection were discovered in the protein coding regions of the fecundity genes through scan. After protein translation 19 variants were discovered; 3 in BMP15, 4 in FOXL2, 2 in GDF9, 3 in MHCDQA1 and 7 in MTNR1A. 11 of the variants carry neutral substitution and are therefore predicted to be functional. Based on the protein analysis 10 out of the 45 animals; TP27F, TF375, TP14F, TN60M, SJ4M, AX1, AX4F, AX3F, AX6F, AX7F were predicted to carry a combination of functional fecundity proteins. A large number of animals within the study population carry chromosomal aberration. Significant genetic diversity exists in the study population and some animals carry defective fecundity protein variants. The presence of chromosomal anomaly and protein polymorphisms, with some variant predicted to carry deleterious amino acid substitutions, may be one of the reasons for fertility decline in the study population. There is evidence of hybridization between R. timorensis Blainville and R. unicolor Kerr. Axis axis Erxleben is likely to have undergone inbreeding and allele fixation. It is concluded that the type of husbandry practiced in PTH Lenggong, Perak, where animals of different breeds are kept together, and the absence of a well-designed breeding program for the deer, might be responsible for these fertility problems.